The Effects of U.S. Sheduled Macroeconomic News Announcements on Stock Market Uncertainty: International Evidence - Appelqvist, Eero (My University, 2008)
The arrival of the new information affects the asset prices. This is one the accepted cornerstones of modern finance theory. This has also laid the foundation for a wide literature investigating the role of information in financial markets. One group of investigating the role of information in financial markets focuses on the effects of scheduled macroeconomic news announcements on different types of markets including equities, bonds and currencies. Previous results in this line of studies have confirmed that scheduled macroeconomic news announcements have significant impact on financial markets, although this impact varies across markets and announcements. The purpose of this thesis is to investigate are releases of scheduled U.S. macroeconomic news announcements affecting uncertainty in different markets in different parts of the world. The example markets investigated in this study are taken from Europe, North -America and Asia. The time period investigated in this thesis is between January 2001 and December 2006. Six important scheduled U.S. macroeconomic announcements are chosen to this study mainly by previous studies. To study the systematic implied volatility reactions around these macroeconomic news announcements in different markets two regression models are constructed. First model examines the impact of scheduled macroeconomic announcements by regressing log percentage changes in implied volatility on a set of dummy variables that identify the days on which these announcements are released. Second model constructed is more advanced regression model which can be used to examine whether implied volatilities react differently to good and bad news. In this second regression the logarithmic percentage changes of the implied volatility of the index are regressed on dummy variables that reflect good and bad news. In general, results of this study are indicating that U.S. macroeconomic figures are still widely followed by investors all around the world and have impact on volatilities implied by option prices.
Keywords: Implied volatility; macroeconomic news announcement; options; market efficiency; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|